Description of a new species of Ituglanis (Siluriformes: Trichomycteridae) from Serra dos Carajás, rio Tocantins basin - WOSIACKI, Wolmar Benjamin (2015)
A new species of Ituglanis is described from the rio Tocantins basin, State of Pará, Brazil. Ituglanis ina, new species, is distinguished from its congeners by the presence of a dark vertical bar over the base of the caudal-fin rays (vs. no bars over caudal-fin base); and by the presence of a middle trunk line of tiny neuromasts extending along the flank until the vertical through the dorsal fin, or near the caudal-fin base (vs. no middle trunk line of tiny neuromasts). Ituglanis ina can be further distinguished by a combination of characters related to color pattern and morphology. Comments on the relationship between Ituglanis species are presented.